2020
DOI: 10.3390/ijms21072403
|View full text |Cite
|
Sign up to set email alerts
|

Novel Autoantibody Signatures in Sera of Patients with Pancreatic Cancer, Chronic Pancreatitis and Autoimmune Pancreatitis: A Protein Microarray Profiling Approach

Abstract: Identification of disease-associated autoantibodies is of high importance. Their assessment could complement current diagnostic modalities and assist the clinical management of patients. We aimed at developing and validating high-throughput protein microarrays able to screen patients’ sera to determine disease-specific autoantibody-signatures for pancreatic cancer (PDAC), chronic pancreatitis (CP), autoimmune pancreatitis and their subtypes (AIP-1 and AIP-2). In-house manufactured microarrays were used for aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
(61 reference statements)
1
9
0
Order By: Relevance
“…To select protein antigens of high interest, a PubMed literature search was performed. The proteins included in the study matched one or more of the following criteria: reported in previous IPMN-related antibody reports [ 22 ], pancreatic cancer-related antibody reports [ 18 , 20 , 23 , 24 , 25 , 26 , 27 ], or cancer autoantibody publications [ 14 , 28 , 29 , 30 ]. Additionally, some proteins of importance to pancreatic function, such as CCKBR, PNLIP, LDH, VEGF, LOX, G6PD, and GPX-4, were included.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To select protein antigens of high interest, a PubMed literature search was performed. The proteins included in the study matched one or more of the following criteria: reported in previous IPMN-related antibody reports [ 22 ], pancreatic cancer-related antibody reports [ 18 , 20 , 23 , 24 , 25 , 26 , 27 ], or cancer autoantibody publications [ 14 , 28 , 29 , 30 ]. Additionally, some proteins of importance to pancreatic function, such as CCKBR, PNLIP, LDH, VEGF, LOX, G6PD, and GPX-4, were included.…”
Section: Methodsmentioning
confidence: 99%
“…Protein microarrays were produced and incubated as described in full detail elsewhere [ 20 , 21 , 32 , 33 ]. Briefly, the cDNAs were used for a PCR-based generation of protein expression templates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low prevalence of PC means that biomarkers should be highly specific[ 164 ]. It is difficult to properly correlate AAbs with PC for diagnostic purposes because of the low immune response to this cancer, attributable to the protection offered by the stromal network and immunosuppressive mechanisms[ 159 - 161 ].…”
Section: Autoantibodiesmentioning
confidence: 99%
“…A further concern is the low capacity of AAbs to differentiate between PC and other inflammatory diseases, especially CP or autoimmune pancreatitis, which are responsible for a large production of AAbs. In this regard, some authors have proposed a panel of PP1R15A, CYP3A5, and WDR45 antigens to discriminate between PC and benign inflammatory disease[ 164 ].…”
Section: Autoantibodiesmentioning
confidence: 99%